Production Inefficiency In Small And Medium Industries: A Study Of Bakery Firms In Malaysia - Shazali Abu, Mansor; Alias, Radam (Universiti Malaysia Sarawak, (UNIMAS), 2000)
Contemporary empirical works on efficiency have focused considerably on the overall effects of productivity. Few have attempted decomposing efficiency effects of productivity. While aggregate studies are useful, efforts to unbundle efficiency effects can offer important insights into the sources of productivity. This not only assists in allowing a better understanding of the role of economic agents, but also in policy making. Using prevailing models of technical and scale-based efficiencies, this paper attempts to examine the dynamics of productivity growth in small and medium scale industries (SMIs). It also compares the composition as well as the overall efficiency of SMIs and large scale industries (LIs). A case study was conducted on the bakery industry in Malaysia.